KELOMPOK MUSIK CV. BINTANG GRUP: MEDIA MERAWAT IDENTITAS ADAT BATAK MELALUI MUSIK DI SOLO RAYA - Barasa, Zepanya Saputra; Setiawan, Aris (Sorai: Jurnal Pengkajian dan Penciptaan Musik, 2024)
Migration is an activity that has become a tradition for the Batak people. The migration destinations extend beyond the island, one of which is in the Solo Raya area. The identity of the Batak community remains preserved during migration because their original customs and culture continue to be an integral part of their daily lives. The purpose of this journal is to explore the cultural life of the Batak community and the steps they have taken to preserve their traditional identity through music, specifically through CV. Bintang Group. The research method used in this journal is qualitative, collecting data through observation, interviews, literature studies, and several other methods. The findings indicate that the Batak community, represented by CV. Bintang Group, has successfully preserved their traditional identity through various means. These include teaching Batak music to their children, participat ing in cultural events outside of traditional Batak ceremonies, possessing a complete set of traditional Batak instruments, and being active on social media. The conclusion of this research is that the Batakcommunity has successfully maintained their traditional identity even while living in distant lands.